Prima Sinyal: A Program to Improve Kindergarten Teachers' Abilities In Early Detection Of Deviations in The Growth and Development of Preschool Children: Prima Deteksi: Program Peningkatan Kemampuan Guru TK dalam Deteksi Dini Penyimpangan Pertumbuhan dan Perkembangan Anak Usia Prasekolah - Roida Simanjuntak, Susi; Nisa, Khairun; Syahputra, Rendy (Universitas Haji Sumatera Utara, 2025)
According to Regulation of the Minister of Health of the Republic of Indonesia Number 66 of 2014, kindergarten teachers have a role in monitoring and detecting growth and developmental issues in children. However, an interview with the principal of Pembina State Kindergarten in Manado revealed that teachers at Pembina State Kindergarten have never conducted early detection of growth and developmental issues in all students. This results in the growth and developmental status of all students at Pembina State Kindergarten in Manado being unknown. The Community Health Center (Puskesmas) has also never visited the school to screen for growth and developmental issues in children. Another identified issue is that the School Health Unit is not equipped with height and weight measuring devices or SDIDTK Kits for screening. Therefore, this program aims to improve the skills of kindergarten teachers in early detection of growth and developmental issues in preschool-aged children through training, mentoring, and the provision of SDIDTK Kits. The training results showed that the majority of teachers experienced an increase in knowledge of more than 80%. Based on pre-test and post-test results, teachers' knowledge scores showed a significant increase. Observation results also showed an improvement in teachers' skills in early detection of growth and developmental issues. In conclusion, there has been a significant improvement in teachers' knowledge and skills in early detection of growth and developmental issues in preschool-aged children.